A detailed exploration of early infant milk feeding in a prospective birth cohort study in Ireland: combination feeding of breast milk and infant formula and early breast-feeding cessation. Issue 4 (14th April 2020) - Hemmingway, Andrea; Fisher, Dawn; Berkery, Teresa; Dempsey, Eugene; Murray, Deirdre M.; Kiely, Mairead E.
Abstract: Breast-feeding initiation and continuation rates in the UK and Ireland are low relative to many European countries. As a core outcome of the prospective Cork Nutrition and Development Maternal-Infant Cohort (COMBINE) study (Cork, Ireland), we aimed to describe infant milk feeding practices in detail and examine the prevalence and impact of combination feeding of breast milk and infant formula on breast-feeding duration. COMBINE recruited 456 nulliparous mothers (2015–2017) for maternal–infant follow-up via interview at hospital discharge (median 3 (interquartile range (IQR) 2, 4) d ( n 453)), 1 ( n 418), 2 ( n 392), 4 ( n 366), 6 ( n 362) and 9 ( n 345) months of age. Median maternal age was 32 (IQR 29, 34) years, 97 % of mothers were of white ethnicity, 79 % were Irish-born and 75 % were college-educated. Overall, 75 % breastfed to any extent at discharge and 44 % breastfed solely. At 1, 2, 4, 6 and 9 months, respectively, 40, 36, 33, 24 and 19 % breastfed solely. Combination feeding of breast milk and infant formula was common at discharge (31 %) and 1 month (20 %). Reasons for combination feeding at 1 month included perceived/actual hunger (30 %), healthcare professional advice (31 %) and breast-feeding difficulties (13 %). Of mothers who breastfed to any extent at discharge, 45 % stopped within 4 months. Mothers who combination fed were more likely to cease breast-feeding than those who breastfed solely (relative risk 2·3 by 1 month and 12·0 by 2 months). These granular data provide valuable insight to early milk feeding practices and indicate that supporting early breast-feeding without formula use may be key to the successful continuation of breast-feeding.